Rupture of the ventricular septum from myocardial infarction: Haemodynamic response to surgical treatment. Issue 1 (January 1969) - Partington, T.; Somerville, Jane; Sellors, T. Holmes; Resnekov, L.
Abstract : A patient aged 59 had a coronary thrombosis complicated by a ruptured ventricular septum. This was successfully repaired surgically about three months after the infarct, and some indications and problems connected with this procedure are discussed.